Pengaruh Karakteristik Informasi Akuntansi Dan Desentralisasi Terhadap Kinerja Manajerial (Studi Pada Palang Merah Indonesia Provinsi Jawa Tengah) - Hestin Yusnita Cahyaningrum; Sri Suprapti (FEB UNTAG Semarang, 2016)
AbstractThe purpose of research is to determine the characteristics of the accounting information that is relevant, reliable, complete, timely, understandable,verifiable and decentralization on manajerial performance at the Indonesian Red Cross (PMI) Central Java Province. The population in this research was Head of Section at the Indonesian Red Cross (PMI) Central Java Province totaling 31 people, which is taken entirely as a sample or said as population research (census). The data used in this research are primary data using quetionnaire method. Analysis of data using multiple linier regression analysis.The result showed that the characteristics of the accounting information that is relevant have positive and significant impact on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Characteristics of accounting information that is reliable have positive and significant impact on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Characteristics of accounting information that is complete have positive and significant impact on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Characteristics of accounting information that is timely have positive and significant impact on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Characteristics of accounting information that is understandable have no effect on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Characteristics of accounting information that is verifiable have no effect on managerial performance at the Indonesian Red Cross (PMI) Central Java Province. Decentralization have positive and significant impact on managerial performance at the Indonesian Red Cross (PMI) Central Java ProvinceKeyword : relevant, reliable, complete, timely, understandable, verifiable, decentralization and managerial performance